Blue : 350 inspiring ways to decorate with blue - Cregan, Lisa. (New York : Hearst Books, 2011)
A complete guide to decorating with any shade of blue. Learn how to showcase blue throughout your home, and mix it with other colors and patterns.
A room-by-room tour of the world of blue -- What works with blue? -- How blue are you?
'House beautiful.'
Includes index.
Keywords: Blue in interior decoration; Color in interior decoration; Interior decoration